A succinct review on the PVDF/Imidazolium-based ionic liquid blends and composites: Preparations, properties, and applications - Shamsuri, Ahmad Adlie; Daik, Rusli; Md. Jamil, Siti Nurul Ain (Multidisciplinary Digital Publishing Institute, 2021)
Poly(vinylidene fluoride) (PVDF) is a versatile thermoplastic fluoropolymer with intriguing characteristics, which is receiving considerable attention from researchers in many areas. Recently, PVDF and its copolymer, such as poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) have been blended with ionic liquids to produce blend and composite materials for target applications. In this succinct review, two types of ionic liquids that are utilized for the preparation of PVDF and PVDF-HFP blends and composites, namely, hydrophilic and hydrophobic imidazolium-based ionic liquids, are reviewed. In addition, the effect of the ionic liquids on the physicochemical properties of the PVDF and PVDF-HFP blends and composites, is described as well. On top of that, a multitude of applications of the blends and composites are also succinctly reviewed. This review may give inspirations to the polymer blend and composite researchers in diversifying the applications of thermoplastic fluoropolymers through the utilization of ionic liquids.